The Influence of Marketing Mix to Consumer Purchasing Decisions DK Donut, Cimindi, Bandung - Rohman, Ngabdur; Rachmawati, Evy (Journal of Business and Management, 2016)
Abstract. This research objective to know the marketing mix of DK Donut Company and the influence of marketing mix toward purchase decision donut. Variables that used are variable marketing mix and variable reseller purchase decision. Questionnaire was done toward 78 respondents that take randomly and be analyzing using SPPS. Researcher also had done observation on production place. The results of this research are DK Donut Company had set marketing mix (product, price, place, and promotion).In product variable, DK Donut Company had produced a product with brand DK Donut. DK Donut’s reseller can use their brands and sell the product with reseller price.In price variable, DK Donut Company decided its product price based on competition based pricing (competitor’s price). In place or distribution variable, DK Donut Company has some reseller who distribute company’s product. DK Donut production place is not strategic so the location is not easy accessible reseller especially reseller by a car. In promotion variable, DK Donut had built billboards to promote the product and brands DK Donut to the reseller/consumer. Variable product and price gives positive influence toward purchase decision significantly. Recommendation to DK Donut Company to make the production place strategic by replace production place (by rent a shop store) which is accessible to all kind of reseller. DK Donut Company has to keep cleanliness production place and do some promotion program to get new reseller and maintain old reseller. Keyword: marketing mix, reseller, purchase decision, DK Donut Company